Laparoscopic Management of Abdominal Trauma - Kedikas, Renatas; Brimas, Gintautas (Lietuvos chirurgija, 2025)
Objective. To review scientific articles dealing with the use of laparoscopy in the treatment of abdominal trauma. Methods. The PubMed database was searched for scientific articles published between 2015-01-01 and 2024-09-01. The search keywords used were: laparoscopy, therapeutic laparoscopy, blunt abdominal trauma, penetrating abdominal trauma. Results. Four articles were included in the final evaluation. Methods, main findings, conclusions and recommendations are presented. Conclusions. Based on the results and conclusions of the published articles, the minimally invasive surgical technique of laparoscopy is an important and effective tool in the diagnosis and management of abdominal trauma. Laparoscopy has advantages over open surgery, including a lower risk of complications, faster recovery and better cosmetic results. It is important to consider the contraindications to laparoscopy and to select patients appropriately for this treatment. Adequate hospital infrastructure and qualified medical staff are also required to ensure the success of the operation. Laparoscopy is an effective treatment option for abdominal injuries, helping to reduce the risk of complications and the length of hospital stay.
Keywords: laparoscopy; therapeutic laparoscopy; blunt abdominal trauma; penetrating abdominal trauma